2015
DOI: 10.1039/c4gc01818d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient hydrogenation of carbon dioxide to methyl formate over supported gold catalysts

Abstract: Transformation of carbon dioxide (CO 2 ) into valuable chemicals is an interesting topic in green chemistry. Hydrogenation of CO 2 to methyl formate (MF) in the presence of methanol is an important reaction. In this work, Au nanocatalysts immobilized on different supports were prepared and characterized by X-ray diffraction (XRD), transmission electron microscope (TEM) and X-ray photoelectron spectrometer (XPS). The catalytic performances of the catalysts for the reaction were studied. It was demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 57 publications
(39 reference statements)
3
37
0
Order By: Relevance
“…Finally,b yt he addition of P(OEt) 3 ,t he high-field hydride signal becamep redominant and no organometallic speciesa ssociated with P-ligands were detected. Indeed, none of the signals coupled with 13 Pb y 1 H, 13 C, or 31 PNMR spectroscopy,t hus reinforcing the decomposition path of P(OEt) 3 into H 3 PO 4 [52] (observed by 31 PNMR) that is an extra source of H + necessary in the protonation step. [32] We have also observed CO and water in the gas phase (by GC) of the reaction of 60 bar = 6MPa CO 2 /H 2 (1:1) at 120 8Cf or 24 h, hence indicatingt he occurrence of RWGS reactiona tt his relative low temperature.…”
Section: Mechanistic Insightsmentioning
confidence: 85%
See 2 more Smart Citations
“…Finally,b yt he addition of P(OEt) 3 ,t he high-field hydride signal becamep redominant and no organometallic speciesa ssociated with P-ligands were detected. Indeed, none of the signals coupled with 13 Pb y 1 H, 13 C, or 31 PNMR spectroscopy,t hus reinforcing the decomposition path of P(OEt) 3 into H 3 PO 4 [52] (observed by 31 PNMR) that is an extra source of H + necessary in the protonation step. [32] We have also observed CO and water in the gas phase (by GC) of the reaction of 60 bar = 6MPa CO 2 /H 2 (1:1) at 120 8Cf or 24 h, hence indicatingt he occurrence of RWGS reactiona tt his relative low temperature.…”
Section: Mechanistic Insightsmentioning
confidence: 85%
“…In contrast, phosphites [i.e.,P (OEt) 3 ]p rovided an improvement in both the catalytic activity and oxo-product selectivity,a sa lso observed by others. [28] However, 31 PNMR experiments revealed that this apparent ligand effect wasc aused by the formation of phosphoric acid (H 3 PO 4 )u nder our reaction conditions. [33] It is reasonable to assume, that even in the case of reactions involving CO 2 /H 2 in imidazolium salt IL media, it will be possible to shift the selectivity towards the CO path by fine-tuning the reaction conditions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[3] Ap otential approach to circumvent this problem is the use of alcohols such as methanoli nstead of water as the solvent to perform CO 2 hydrogenation. [14] Most recently, Urakawa and co-workers demonstrated the continuous hydrogenation of CO 2 to MF in af ixed-bedr eactorc atalyzed by aS iO 2 -supported Ag catalyst. [4] In contrast to formic acid, the resulting MF can be readilyd istilledf rom the product mixture owing to its very low boilingp oint (31.7 8C) as well as its negligible bondingw ith bases.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In 2015, Wu et al reported an impressive TOF of up to 534 h À1 by using ZrO 2 -supported Au nanoparticlesi nt he absence of base under harsh conditions (200 8C, 160 bar). [14] Most recently, Urakawa and co-workers demonstrated the continuous hydrogenation of CO 2 to MF in af ixed-bedr eactorc atalyzed by aS iO 2 -supported Ag catalyst. 100 %s electivity towards MF at a methanol conversion of 4% waso btained at 280 8C and 300 bar with ag as hourly space velocity (GHSV) of 9000 h À1 .…”
Section: Introductionmentioning
confidence: 99%